Impact of Mg2+ substitution on structural, magnetic and optical properties of Cu-Cd ferrites. (2022) - Bagade, Arun; Nagwade, Pratik; Nagawade, Arvind; Thopate, Shankar; Pandit, Vikram; Pund, Sangita
Abstract: The Mg 2+ doped Mgx Cu0.5-x Cd0.5 Fe2 O4 [x = 0.0 to 0.5, Δx = 0.1] ferrites were produced utilising an oxalate precipitant and a co-precipitation technique. Fourier Transform Infrared spectroscopy (FT-IR) and Thermogravimetry (TG) were used to characterise the produced oxalate precursor powders. The structural, magnetic, and optical properties of prepared final ferrites were investigated using X-ray diffraction (XRD), FT-IR, Vibrating Sample Magnetometer (VSM), and UV–Vis Diffuse Reflectance Spectroscopy (UV–Vis DRS) techniques. The development of cubic spinel ferrite structure was confirmed by XRD signals. XRD data was used to calculate various characteristics such as crystallite size, theoretical and experimental lattice constants, unit cell volume, and X-ray density. With increasing Mg 2+ doping, the values against lattice parameter (both experimental and theoretical) and unit cell volume show a rising trend, whereas the values against X-ray density show a decreasing trend. Ionic radii (rA and rB ), bond lengths (A-O and B-O), hopping lengths (LA and LB ) and anion-anion distance (dtet, shared doct and unshared doct ) are also reported. FT-IR spectra of synthesized ferrite powders revealed two distinct bands in the ranges of 555 to 579 cm −1 and 414 to 476 cm −1, revealing ferrite's typical features. The FT-IR data was also used to calculate force constants and Debye temperatures for produced ferrite powders, and the results were consistent with the literature. VSM is also used to investigate the magnetic behaviour of synthesized ferrites. Finally, all samples' absorption spectra and energy band gaps are investigated using UV–Vis DRS. Using Tauc's relation, the optical band gaps of Mg-Cu-Cd ferrites samples were computed.